KAJIAN KELAYAKAN FINANSIAL PARIWISATA PANTAI TLANGOH DI KABUPATEN BANGKALAN - SILFI QOTRUNNADA; ELYS FAUZIYAH (Universitas Mahasaraswati K. Mataram, 2023)
Tlangoh Beach is classified as a tourist attraction in Bangkalan Regency, which has only been managed in the last five years. The existence of Tlangoh Beach is naturally quite attractive, with white sand conditions, a long coastline, and not too big waves. This condition inspired the management of the Village Owned Enterprise (BUMDes) of Tlangoh Village, together with the Tourism Awareness Group (Pokdarwis) to develop and complete its supporting facilities. However, BUMDes do not yet know the extent of the business feasibility of the investments made. This study aims to analyze the feasibility level at Tlangoh Beach, Tlangoh Village, Tanjung Bumi District, Bangkalan Regency. The sample in this study is a beach manager consisting of a chairman, secretary, and members. The instruments used to assess the financial feasibility of the Tlangoh Beach management business are NPV, IRR, R/C ratio, B/C ratio, and payback period. The results of the financial analysis show that for the four instruments, the business of developing Tlangoh Beach tourism is very feasible. In addition, the investment value can be closed within 1 year and 2 months.